Peranan Pendidikan Agama Islam dalam Meningkatkan Motivasi Pembelajaran dan Pembinaan Karakter Mahasiswa Pasca Covid 19: - - faqihatin faqihatin (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
In the implementation of face-to-face (offline) classes, it is very necessary for all parties so as not to be trapped in the limitations of using smartphones, limited pulses, limited time, and limited communication. This communication limitation causes limitations in capturing information provided by lecturers or lecturers, especially in the context of character planting. The role of Islamic religious education is an important of character education in re instilling character education in students and also increasing student learning motivation. It is hoped that student learning motivation will grow again as well as efforts in fostering student character.From learning activities carried out with intensive lecture and discussion methods, students are more motivated in implementing learning and sharpening knowledge about worship practices that will lead to better Muslim character building.